The synthesis and characterisation of novel ferrocenyl polyphenylenes - WATSON, GRAEME; DRAPER, SYLVIA (My University, 2012)
This work describes the synthesis and characterisation of a new series of polyphenylenes with up to four ferrocenyl moieties. The synthetic route involves the preparation of a number of novel precursors. Cyclopentadienones, generated from the two-fold Knoevenagel condensation of di-ferrocenyl propanones and diketones, are used in [2 + 4] Diels ? Alder cycloadditions with appropriately substituted acetylenes. 13 is amongst the compounds isolated. It is the largest ferrocenyl-supported polyaromatic hydrocarbon (PAH) to date. Prepared via a Sonogashira cross-coupling reaction between ethynyl-Fc and iodo-HBC, it comprises a hexa- peri -hexabenzocoronene (HBC) core linked via acetylene to a ferrocenyl unit (Fc). The electrochemical and absorption properties of the ferrocenyl-polyphenylenes and the fully conjugated 13 are discussed. The NLO data for 13 , determined by hyper Rayleigh scattering techniques, are compared to those of similar fulleryl-based compounds in the literature.
PUBLISHED
Keywords: Absorption property; Cyclopentadienones; Diels-Alder cycloadditions; Diketones; Ferrocenyl; Hexa-peri-hexabenzocoronenes; Hyper Rayleigh scattering; Knoevenagel condensation; Novel precursors; Polyaromatic hydrocarbons; Polyphenylenes; Sonogashira cross-coupling reaction; Substituted acetylenes; Synthetic routes; Absorption property; Cyclopentadienones; Diels-Alder cycloadditions; Diketones; Ferrocenyl; Hexa-peri-hexabenzocoronenes; Hyper Rayleigh scattering; Knoevenagel condensation; Novel precursors; Polyaromatic hydrocarbons; Polyphenylenes; Sonogashira cross-coupling reaction; Substituted acetylenes; Synthetic routes; Nanoscience & Materials; Smart & Sustainable Planet